Historical overview and challenges in the development of bioarchaeology in Japan - Nagaoka, Tomohito (Frontiers in Earth Science, 2023)
Archaeological human skeletons provide direct evidence of the physical features, lifestyle, diseases, mortality, and health of our ancestors. Bioarchaeology explores population-based trends that vary according to subsistence, social stratification, urbanization, and industrial development. The first systematic bioarchaeological studies in Japan were those on medieval human skeletons in Kamakura City, Japan, in 2003. However, most anthropological studies have focused on the origin and population history of the Japanese since the end of 19th century. Moreover, the number of bioarchaeological studies in Japan is far lower than that in North America, Europe, and Latin America. This paper reviews the history of bioarchaeological research in Japan and discusses the problems associated with its development.